Arcuate line hernia: a case report. Issue 2 (27th February 2023) - Cohen, Koral; Kolwitz, Christine; Petrone, Patrizio; Halpern, David
Abstract: Arcuate line hernias are a rare type of hernia with limited publications regarding their successful repair. The arcuate line is the inferior limit of the posterior leaf of the rectus sheath. An arcuate line hernia is a type of intraparietal hernia, meaning it is not a truly complete fascial defect of the abdominal and, therefore, may present with atypical symptoms. Although published data on arcuate line hernia repairs are limited to a handful of case reports and one literature review, reports regarding robotic repair are exceptionally rare. This case report is the second documented robotic approach to arcuate line hernias known to these authors.